The Use of Reading Comprehension Strategies and their Effects on Academic Achievement of Students A Case Study - Nargis Nadeem; Irfana Omar (University of Management and Technology, 2018)
The purpose of this study was to identify the types of reading strategies used by first year college students for reading different materials and their effects on students' academic performance/achievement. The sample of the study consisted of 269 first year students of different departments of Arts and Humanities group at Government College (Wahdat Road), Lahore. IELTS' Reading Comprehension Test (Academic/General) was used to assess the reading comprehension skills of students. Meta Comprehension Strategy Index (MCSI) by Schmitt (1990) was used to assess the level of awareness and the use of reading comprehension strategies. Data was analyzed using SPSS and was graphically presented to provide a clear understanding of results which indicated the lack of awareness about reading comprehension strategies as a key factor leading to the poor performance of students in the reading comprehension test. The study contributes scholarly in the existing literature by accentuating the need to make instruction about reading strategies compulsory in English language classrooms. It will increase the academic success of students and will also provide them with better job opportunities in future.